INADEQUACIES OF LEGAL DISCOURSE IN SOCIAL AND ONLINE ACTIVISM: EXPLORING REASON AND EMOTION ON INTERNET GOVERNANCE - Pasquot Polido, Fabrício B; Costa dos Anjos, Lucas (Revista Internacional de Pensamiento Político, 2018)
The paper analyzes the relationship between law, reason and emotion in the light of recent changes in the field of social and online activism, particularly with regard to social interactions within digital networks. With the consolidation of the Internet, freedom of expression gave rise to several social phenomena throughout the world, from the Arab Spring uprisings in Africa and in the Middle East, to Wall Street protesters occupying parks in New York City. Internet tools and social platforms have been enabling an array of forms of social mobilization. Under contemporary law, digital interactions decreased the distance between users and information, allowing citizens to better claim rights, organize protests, express political views and identify peers with similar interests online. However, it also hampered the establishment of traditional face-to-face social relations, raising the awareness of the importance of transparency, compliance and information mechanisms related to the origin of online posts and online profiles. In many jurisdictions, legal mechanisms have been put into force to make more stringent liability rules, condemn users, take down webpages and remove allegedly offensive content. In different trends, online activism can be purported as wrongful and even criminalized, whereby digital freedom is considerably restricted. Such governmental stance can bring about the derangement of civil liberties and freedom of speech. In an evergrowing online community, it is particularly relevant for Internet users to be able to express themselves freely and to have their civil rights assured in digital environment. In view of that broader spectrum, the paper discusses the urgent needs for legal institutions and the Internet community to gather efforts in order to ensure that freedoms and users rights are properly safeguarded. What is the proper legal framework for protection of online users interests? Would it foster development, freedom of speech and democratic values? What is the role played by law under the aegis of the world wide web and contemporary society at a national, regional and global level?